Metaphor and its Semantic Representations in the Contemporary Iraqi Theatrical Text - AI–Zaidi, Hassanein Ali Hilo; Abdalyama, Harith H. (Al-Adab Journal, 2021)
Language can be communicated and expressed through semantic indications of signs to create a concept that expands meaning. It enables to make style of various linguistic patterns as language is a literary subject. So, the theatrical field is among the most productive and the most fields that overlap ideas and could expand meanings and indications. Metaphor is one of the important rhetorical concepts that the writers use to keep pace with the development and comprehensive changes in life since theater is a fertile field for the process of functioning metaphor and giving the ability to expand the meaning, form interpretive connotations based on overlapping within the structure of the theatrical text. The researcher tries here to throw light on the most important representations of metaphor in the Iraqi theatrical text. This work includes four sections. Section one includes methodological construction, research problem, how we need it, aiming to identify metaphor and its representations in the Iraqi theatrical text, as well as the limits of the research and defining terminology. The second chapter included two topics: the concept of metaphor, and metaphor in the theatrical text, the chapter concluded with theoretical framework indicators. The third chapter covers the research procedures that include the research community as the researcher relied on the indicators of a theoretical framework with the sample analysis, chosen intentionally. Chapter four introduces research results, conclusions, a list of sources and references.